Knowledge-Based Approaches to the Theory of the Firm: Some Critical Comments - Foss, Nicolai J. (Organization Science, 1996)
It is argued that Kogut and Zander (Kogut, B., U. Zander. 1992. Knowledge of the firm, combinative capabilities, and the replication of technology. Organ. Sci. 3 383–397.) and Conner (Conner, K. R. 1991. A historical comparison of resource-based theory and five schools of thought within industrial organization economics: Do we have a new theory of the firm? J. Management 17 121–154.) erred in the specific way in which they claimed that a distinct theory of the multi-person firm can be constructed on the basis of a theory of organizational knowledge or from resource-based insights. It is not possible to tell very much of a story about why there should be firms in lieu of notions such as “opportunism” or “moral hazard.” However, properly interpreted, knowledge-based theories may help shed light on issues relating to the boundaries and internal organization of the firm.